Populism in the American West: An Enduring and Evolving Trend - Nathalie Massip (IdeAs)
This article aims to appraise the populist strain that has characterized the American West since the late 19th century. Populism, as a political movement, was born in the South and West of the United States. This “prairie populism” allowed the People’s party to score quite a few electoral victories in the 1890s. While the party’s influence waned rapidly, outbursts of populism have animated the West since then. In spite of the centrality of the “people”—and its opposition with “the elite”—as the major definitional element that binds these various expressions of populism together, 21st-century western populism has little in common with its late 19th-century counterpart. The purpose of this essay is to analyze the evolution of western populism, from the People’s party to the late 1970s Sagebrush Rebellion and the People for Constitutional Freedom. Attention is paid to each movement’s emphasis on the “people” as the element at the core of their rhetoric. In addition, this study reveals how this key element has evolved throughout the 20th century, and in what ways today’s populism seeks to defend the interests of a much more limited group. Finally, a close reading of the goals and achievements of each movement offers a better understanding of this evolution from left-wing to right-wing populism.